TAX BURDEN ON COMPANIES IN THE OIL AND GAS INDUSTRY OF THE RUSSIAN FEDERATION: DAMPING MECHANISM VS TAX MANEUVER - M. A. Valishvili (Publishing House of the State University of Management, 2019)
The volatility of hydrocarbon prices on world markets, as well as the high level of dependence of the state budget on oil and gas revenues, are the main conditions for assessing the effectiveness of tax regulation in the oil and gas sector. It should be considered, that, according to the General Scheme for the development of the oil industry of Russia up to 2035, a significant (up to 35%) reduction in oil production at the developed fields, which currently account for more than 70% of the total production, is predicted. Thus, it is necessary to find the optimal balance of the interests of the state, expressed in increasing the tax burden as a source of state revenues and business interests in capital investments in the development of deposits in the initial stages of development.